2007
DOI: 10.4161/psb.2.5.4460
|View full text |Cite
|
Sign up to set email alerts
|

ROS Signaling in Seed Dormancy Alleviation

Abstract: Reactive oxygen species have been suggested to play a signaling role in seed dormancy alleviation. When sunflower seeds become able to fully germinate during dry after-ripening, they accumulate high amount of hydrogen peroxide and exhibit a low detoxifying ability through catalase, resulting from the decrease in CATA1 transcript. ROS accumulation entails oxidative modification of soluble and storage proteins through carbonylation, which suggests that this process might play an important role in plant developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…In general, increases in ROS are required for seed germination (Ogawa and Iwabuchi 2001;Bouteau et al 2007;Bouteau and Bailly 2008). For example, previous data have shown that the inhibition of catalase (a H 2 O 2 scavenging enzyme) can accelerate dormancy release (Hendricks and Taylorson 1975).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In general, increases in ROS are required for seed germination (Ogawa and Iwabuchi 2001;Bouteau et al 2007;Bouteau and Bailly 2008). For example, previous data have shown that the inhibition of catalase (a H 2 O 2 scavenging enzyme) can accelerate dormancy release (Hendricks and Taylorson 1975).…”
Section: Discussionmentioning
confidence: 97%
“…ROS play a key role in various events of a seed's life (Ogawa and Iwabuchi 2001;Bouteau et al 2007;Bouteau and Bailly 2008). In orthodox seeds, ROS are produced at all stages, from embryogenesis to germination (Bailly 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In sunflower (28) and apple (12) seeds, stimulation of seed germination by application of KCN was mediated by ROS. It has further been shown that the gene expression changes occurring upon treatment with either KCN or with the ROS-generating methyl viologen were very similar (6). We therefore hypothesized that the phytotoxicity of bacterial volatiles might be linked to oxidative stress.…”
Section: Vol 77 2011 Hcn and Phytotoxicity Of Bacterial Volatiles 1005mentioning
confidence: 99%
“…New evidence suggests that ROS is not only a cytotoxic molecule, but also emerges as a key regulator in seed physiology where ROS mediates seed germination (Bailly 2004; El-Maarouf-Bouteau et al 2007; Bailly et al 2008; Ye et al 2012). An optimal range of ROS level is required for successful germination.…”
Section: Introductionmentioning
confidence: 99%